Hubungan Pengetahuan, Sikap, dan Perilaku Konsumsi Makanan Tinggi Natrium terhadap Kejadian Prehipertensi pada Mahasiswa: Systematic Literature Review - Alya Rahmadhona (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Prehypertension among university students represents a transitional cardiovascular condition with significant potential to progress toward established hypertension, warranting increasing attention within the domain of public health. This study aimed to analyze and synthesize scientific evidence regarding the relationship between knowledge, attitudes, and dietary sodium consumption behaviors with the occurrence of prehypertension among university students through a Systematic Literature Review (SLR) approach. Literature searches were conducted across Google Scholar, PubMed, and Portal Garuda databases using the PRISMA framework, yielding ten articles that fulfilled the inclusion criteria, published between 2022 and 2025, employing cross-sectional, descriptive, and quasi-experimental designs. Narrative synthesis revealed that students' knowledge levels regarding sodium-related health risks were generally categorized as adequate, yet a persistent knowledge-practice gap was consistently identified across studies. Attitudes toward sodium consumption exhibited moderate and sociodemographically influenced patterns, with associations to prehypertension largely indirect in nature. Sodium consumption behavior demonstrated the strongest and most consistent association with prehypertension incidence, yet proved most resistant to modification through educational interventions. It is concluded that prehypertension prevention strategies targeting university students necessitate multidimensional approaches that prioritize sustained behavioral modification, extending beyond mere enhancement of cognitive knowledge.